Rebuilding of bone tissue around titanium implants after application of low-intensity pulsed ultrasound at different stages osteoreparation (experimental study) - Malyshkina, Svitlana; Makolinets, Vasyl; Nikolchenko, Olga; Grashchenkova, Tamara; Ivanov, Gennadiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
to perform a comparative analysis of the structural organization of the femur with titanium implant in rats after exposure to pulsed ultrasound with intensity 0.4 W/cm2 applied at different stages of osteoreparation. Methods: In 20 rats six months of age (group 1) effect of ultrasound (10 sessions 5 min) we started from the 3rd day after the implantation of titanium samples (BT 16), i.e. at the end stage of traumatic inflammation, and in the remaining 20 animals (group 2) — on the 7th day, at the stage of tissue structures regenerate formation and differentiation of different types of connective tissue. The animals were taken out of the experiment after 7, 14, 30 and 45 days after implantation in terms that correspond to different stages of reparative osteogenesis. Dedicated femur fragments with titanium implants studied by the methods of histology with histomorphometry (thickness of connective tissue capsule around the implant perimeter, area of newly formed tissue around it, the length of the surface of the bone trabeculae occupied by active osteoblasts, the rate of osseointegration, which characterizes the length of the direct contact with the surface of the implant with bone). Results revealed that the use of pulsed ultrasound on the 3rd day after the operation positively influents on the recovery of bone around titanium implants that appears with more active restructuring of granulation tissue to fibroretykular and bone in the early stages of osteoreparation, and determines on the later stages faster formation of mature bone with plate structure than in the case of ultrasound using on the 7th day. On the 45th day of the study it was not found expressed preferences between the groups according to bone morphometric parameters while osseointegration rate in group 1 was 7.5 % higher than in the second. Thickness of dense connective tissue formed on the edge of contact with the implant in all periods of observation was lower in animals of group 1.